Genetic Polymorphism of CYP2D6 and MDR1 in breast cancer patients treated with tamoxifen - Mohamad, NI; Ismail, S; Hamzah , S; Harun, R; Ngow , Harris Abdullah (2010)
Introduction: Tamoxifen is the drug of choice for the treatment of breast cancer patients who are positive for estrogen receptor. It is metabolized by Cytochrome P450 2D6 (CYP2D6) and the variations in CYP2D6 activity has been reported to have important therapeutic consequences which include development of adverse events or therapeutic failure in susceptible individuals. Tamoxifen is known to inhibit P-glycoprotein while active metabolite of this drug activates the expression of MDR1 in MCF-7 cells (ref). This affects the intracellular concentrations tamoxifen and its active metabolites inside the tumour cells. Understanding the impact of this variability is useful to determine the choice and monitor response to therapy. Materials and methods: The study protocol is approved by the Medical Research Ethics Committee and local institutions. Genotyping methods for CYP2D6 and MDR1 were developed using multiplex allele specific PCR (ASPCR) approach. Selected samples were randomly sent for direct sequencing for validation of the ASPCR results. Twenty (20) breast cancer patients were screened for CYP2D6 (CYP2D6*4, CYP2D6*10, CYP2D6*14) and MDR1 ( G2677A/T, C3435T and C1236T). Result: CYP2D6*4 and CYP2D6*14 was absent in patients. The most common variants detected is CYP2D6*10 with 25% of homozygous CYP2D6*10/*10 and 45% heterozygous CYP2D6*1/*10 in breast cancer patients. Heterozygous C3435T was present at the highest frequency at 60%. G2677A/T and C1236T was found in 44.4% and 50% of the 18 samples successfully amplified. Discussion & conclusion: More than half the patients carry CYP2D6*10 and MDR1 variants which reduce the metabolic activity and expression of the efflux transporter. However, the clinical implications of the variation in dose adjustment and therapeutic effect require further confirmation from the ongoing study with a larger sample size. Keyword : CYP2D6, MDR1, Breast cancer